Determination of Free Levels of Cinitipride in Human Plasma by Liquid Chromatography-Tandem Mass Spectrometry - Shikha M. N. Roy; Santos H. M. Yetal; Sangita V. Chavan; Vara D. R. Pradhan; Santosh S. Joshi (E-Journal of Chemistry)
A rapid, sensitive and specific method to quantify cinitapride in human plasma using risperidone as the internal standard is described. Sample preparation involved simple solid phase extraction procedure. The extract was analyzed by high performance liquid chromatography coupled to electrospray tandem mass spectrometry API-4000 (LC-MS/MS). Chromatography was performed isocratically on Thermo Hypurity C18 analytical column, (50 mm x 4.6 mm, 5 µm i.d.). The assay of cinitapride was linear calibration curve over the range 20.118 pg mL−1 to 2011.797 pg mL−1. Plasma concentrations of cinitapride were determined by LC-MS/MS with a limit of quantification of 20.118 pg mL−1 that allowed an appropriate characterization of the pharmacokinetic profile of cinitapride at the therapeutic dose. The method was successfully applied to the bioequivalence study of cinitapride tablet (1.0 mg) administered as a single oral dose.